the problem is:

(x^2 - y^2)^2 / x^2 + 2xy + y2

the answer is supposed to be:

x^2 - 2xy +y2

i get to x^2 - 2x^2y^2 + y^2 / 2xy

what am i missing?

thanks

Printable View

- Feb 19th 2009, 08:55 PMcornmanneed help with basic algebra problem
the problem is:

(x^2 - y^2)^2 / x^2 + 2xy + y2

the answer is supposed to be:

x^2 - 2xy +y2

i get to x^2 - 2x^2y^2 + y^2 / 2xy

what am i missing?

thanks - Feb 19th 2009, 09:07 PMmollymcf2009
- Feb 19th 2009, 09:10 PMADARSH

$\displaystyle

{(x^2-y^2) =(x+y)(x-y)}

$

$\displaystyle

{(x+y)^2 = (x^2 +2xy +y^2) }

$

$\displaystyle

{(x-y)^2 = (x^2-2xy +y^2)}

$

$\displaystyle

(x^2-y^2)^2 =(x+y)^2(x-y)^2...........\text{Use in numerator}

$

$\displaystyle

(x^2 +2xy +y^2)= (x+y)^2 ...........\text{Use in denominator}

$

$\displaystyle

(x^2-2xy +y^2)=(x-y)^2 ...........\text{use in the last step}

$